Coordinative diversity in mononuclear CuI and CuII complexes of O,N,S-ambidentate camphoriminoquinone ligands - Filippou, Vasileios; Bubrin, Martina; Grupp, Anita; Ringenberg, Mark R.; Kaim, Wolfgang (Inorganica Chimica Acta, 2022)
[Display omitted] •Camphoriminoquinones can act as ligands towards CuI and CuII.•Copper prefers O,N chelation with long Cu···O bonds in both cases.•An additional thioether function leads to Cu-S coordination.•CuII complexes exhibit variable structural distortion. The ligands N-phenylcamphoriminoquinone 1 and N-(2-thiomethylphenyl)camphoriminoquinone 2 were reacted with copper(I) and copper(II) precursors to yield structurally characterized compounds with N-, O,N-, N,S- and O,N,S-coordination: [CuI(1-κ2O,N)(dppf)](PF6) 3(PF6), [CuI(2- κ2N,S)(dppf)](PF6) 4(PF6), [CuII(1- κN)(NO3– κO)2] and [CuII(1-κ2O,N)(NO3-κO)2] 5, and [CuII(2-κ3O,N,S)(NO3-κO)2] 7 where dppf is 1,1′-bis(diphenylphosphino)ferrocene. Spectroelectrochemistry reveals that the cations 3+ and 4+ exhibit ferrocene-based oxidation and camphoriminoquinone-centered reduction. The copper(II) compounds 5 and 7 exhibit coordinative variety with monodentate and bidentate coordination of the ligand 1 for two different molecules in 5, and with O,N,S-tridentate coordination for 2 in 7.